Impact characteristics of a badminton racket with realistic finite element modeling - Yin, S. R.; Chang, H. C.; Cheng, K. B. (Proceedings, 2020)
The tension of strings on a badminton racket can be adjusted by players according to their personal experiences. The best way to execute such an adjustment remains unclear. A finite element model was employed in this study to investigate the effect of having nonuniform string tension on string-bed deformation, and the direction of force applied to shuttlecock head upon impact. The racket model was based on a commercially available racket with a simplified string-bed of 16 strings established using SolidWorks. A displacement was applied to the ball to simulate impacting on the string-bed. The simulations revealed that slightly lowering the tension of off-centered strings had a minimal effect on the von Mises stress distribution of the ball and string-bed. The off-centered impact caused comparable contact force magnitude but altered force direction. Further investigation is needed for understanding the effect of varying string tension on badminton racket performance.